What is Role of Size on Company Value - Soukotta, Agnes; Wihelmina Silooy, Revi; Yuniarti Layn, Yuyun (Yayasan Pendidikan Belajar Berdikari, 2024)
The purpose of this study is to look at how liquidity, solvency, company size, and the fraction of independent board of commissioners affect corporate value. The population used includes pharmaceutical subsector companies listed on the Indonesia Stock Exchange between 2020 and 2023, with a total research sample of 48 companies collected using purposive sampling approaches (with particular criteria). The study hypothesis was tested using a multiple linear regression model with a t-test α of 4%. The following approaches were used: descriptive analysis, normality test, autocorrelation test, heteroscedasticity test, and multicollinearity test. The findings of this study indicate that liquidity has a positive effect on company value, solvency has a good effect on company value, firm size has no effect on company value, and an independent board of directors has a positive influence on company value. It is intended that the implications of the results of this research can help potential investors decide whether to invest in a company.